1982
DOI: 10.1111/j.1365-2559.1982.tb02711.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface antigen in glomerular immune complex deposits of patients with systemic lupus erythematosus

Abstract: In view of a high prevalence of hepatitis B virus infection in the Malaysian population, indirect immunofluorescence examination for hepatitis B surface antigen (HBsAg) was routinely performed on renal biopsy specimen at the University Hospital, Kuala Lumpur, over a 3-year period. Examination of renal tissue from 259 patients, including 47 with systemic lupus erythematosus (SLE), revealed 43 cases with HBsAg in glomerular immune complexes. A significantly high proportion (30/43) of these were SLE patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The association between chronic HBV infection and focal segmental glomerulosclerosis, minimal change nephropathy [37, 52, 53]and lupus nephritis may be fortuitous [54, 55]. …”
Section: Pathology Of Hbv-associated Glomerulonephritismentioning
confidence: 99%
“…The association between chronic HBV infection and focal segmental glomerulosclerosis, minimal change nephropathy [37, 52, 53]and lupus nephritis may be fortuitous [54, 55]. …”
Section: Pathology Of Hbv-associated Glomerulonephritismentioning
confidence: 99%
“…As an additional line of evidence relating HBV antigens and lupus kidney disease, Looi and Prathap (1982) reported that HBV-associated antigen deposition was found in the renal tissue of 63.8% (30/47) of lupus patients. Consistent with their report, Wang et al (2012) demonstrated that HBV-associated antigen deposition was present in 50.6% (84/166) of renal biopsies from lupus patients.…”
Section: A Role Of Hbv Infection In the Pathogenesis Of Slementioning
confidence: 99%
“…Many extrahepatic manifestations are recognized in patients with HBV, including glomerulonephoritis, arthritis, vasculitis, and cryoglobulinaemia, features which are also frequently seen in SLE patients. It is possible that the HBV induces the lupus syndrome in susceptible individuals [58].…”
Section: Hbv and Slementioning
confidence: 99%
“…Based on evidence of the presence of HBsAg in glomerular immune complexes in patients with renal disease of varying morphological patterns, including membranous, proliferative and mesangiocapillary glomerulonephritis and focal glomerulosclerosis, Looi et al [58] aimed to find the frequency of HBsAg immune deposits in lupus nephritis. Over a 3-year period, they examined renal tissue from 259 patients, including 47 with SLE.…”
Section: Hbv and Slementioning
confidence: 99%